NILAI-NILAI SOSIAL NOVEL “SORDAM” KARYA SUHUNAN SITUMORANG - Aisyah, Siti; Jaya, Wayan Satria; Surastina, Surastina (Lembaga Penelitian UM Metro, 2016)
This study aims to identify and describe the social values in Sordam novel by Suhunan Situmorang. The researcher cited the data in the form of sentences, paragraphs and dialogues that contained in the novel which has some social values such as positive social and negative social values. The method that used in this research was descriptive qualitative method with content analysis technique, that is by analyzed the letters, words, sentences and verse that can explain some social values in this novel. Since the data that analyzed was in the form of sentences and qualitative, the authors used qualitative data analysis, based on the content and structure of the existing sense. Therefore, in analyzing the data and drawing the final conclusion, the authors used formulas statistical and hypothesis testing. Based on the research finding and discussion, it concluded that there were 72 quotations in Sordam novel by Suhunan Situmorang that containts of two social values, the first is positive social values and the second negative social values. The researcher suggested the reader and students to further study in various theories related to social values in a novel in order to broaden the knowledge of the readers and not just read the novel as an alternative entertainment.